1998
DOI: 10.1083/jcb.143.6.1635
|View full text |Cite
|
Sign up to set email alerts
|

AIR-2: An Aurora/Ipl1-related Protein Kinase Associated with Chromosomes and Midbody Microtubules Is Required for Polar Body Extrusion and Cytokinesis in Caenorhabditis elegans Embryos

Abstract: An emerging family of kinases related to the Drosophila Aurora and budding yeast Ipl1 proteins has been implicated in chromosome segregation and mitotic spindle formation in a number of organisms. Unlike other Aurora/Ipl1-related kinases, the Caenorhabditis elegans orthologue, AIR-2, is associated with meiotic and mitotic chromosomes. AIR-2 is initially localized to the chromosomes of the most mature prophase I–arrested oocyte residing next to the spermatheca. This localization is dependent on the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
282
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(299 citation statements)
references
References 70 publications
17
282
0
Order By: Relevance
“…However, consistent with the well documented requirement for Aurora B kinase for chromosome segregation (Schumacher et al, 1998;Adams et al, 2001b;Giet and Glover, 2001;Ditchfield et al, 2003;Hauf et al, 2003), a functional rescue, as judged by the ability of the transfected cells to recruit the spindle checkpoint component BubR1 (Ditchfield et al, 2003;Hauf et al, 2003) or to form a properly aligned metaphase plate, was not observed in INCENP siRNA-treated cells that had been transfected with GFP-INCENP 1-58 (Figure 6, D and E).…”
Section: Ectopic Gfp-incenp 1-58 Cannot Functionally Rescue Incenp Simentioning
confidence: 51%
“…However, consistent with the well documented requirement for Aurora B kinase for chromosome segregation (Schumacher et al, 1998;Adams et al, 2001b;Giet and Glover, 2001;Ditchfield et al, 2003;Hauf et al, 2003), a functional rescue, as judged by the ability of the transfected cells to recruit the spindle checkpoint component BubR1 (Ditchfield et al, 2003;Hauf et al, 2003) or to form a properly aligned metaphase plate, was not observed in INCENP siRNA-treated cells that had been transfected with GFP-INCENP 1-58 (Figure 6, D and E).…”
Section: Ectopic Gfp-incenp 1-58 Cannot Functionally Rescue Incenp Simentioning
confidence: 51%
“…3b). These genes have known roles in spindle midzone formation and completion of cytokinesis [17][18][19] . After ASS the aster-positioned furrow ingressed weakly compared with wild-type embryos.…”
Section: Henrik Bringmann 1 and Anthony A Hymanmentioning
confidence: 99%
“…In yeast, Ipl1 is normally localized to the spindle pole body (8), and, during mitosis, it is mainly associated with the kinetochore and the mitotic spindles (9). In C. elegans, AIR-1 is localized at the centrosomes (10), while AIR-2 is localized at the kinetochore and midbody (11). In Drosophila, only the centrosome-associated Aurora-A has been thoroughly studied (12).…”
mentioning
confidence: 99%